Disruptive innovations and its impact on public sector banks in India - N, Devaraju; B.N, Prathap (BOHR International Journal of Advances in Management Research, 2023)
The banking sector has incorporated emerging changes to meet customer requirements and enhance growth. Merger and acquisitions are one of the major changes in the banking industry. Mergers and acquisitions have created scope for the adoption of disruptive inventions in banking technology. The adoption of financial technology (FinTech) over recent years has changed the landscape of Indian public sector banks. These disruptive innovations improve the performance, efficiency, and quality of services of public sector banks. Technological innovation in banking has increased the competency level of public sector banks. Customers are interested to adopt these disruptive inventions because the electronic mode is having more scope and is convenient for them. This study identifies the financial progress and inventions in the banking sector. The study aims to know the changes brought by disruptive technologies on the services of public sector banks.